PENGARUH BRANDING AND PACKAGING TERHADAP KINERJA SOSIAL DAN EKONOMI MUSEUM SONOBUDOYO SEBAGAI DAYA TARIK WISATA DAERAH ISTIMEWA YOGYAKARTA - Rezi Edi Muin (Pringgitan, 2020)
Museum as one of the tourist attraction that has its own potential as a window to the world through a collection - a collection of cultural relics and historical form. Yogyakarta as a city of culture and history has such appeal through Sonobudoyo, this museum is a museum that has the most complete collection in Yogyakarta, (data Directorate of Preservation of Cultural Heritage and Museums Kemendikbud RI, 2014). Currently Sonobudoyo optimally not yet felt its role as a museum. It is based because Sonobudoyo in performance has not run optimally. So, we need studies that affect the performance of Sonobudoyo This study aims to determine the existing condition Sonobudoyo performance. From these results we can measure the extent of the influence of branding and packaging of the performance of the museum. This research uses descriptive qualitative and quantitative methods to determine the performance of existing Sonobudoyo by analyzing the influence of branding and packaging of the performance Sonobudoyo.Keywords: Tourism Attraction, Museum Performance, Tourism Marketing, Branding & Packaging